Utilization of Livestock Waste as Biochar and Poschar to Increase Soil Organic Matter and Red Chili Yields - Yohanes Parlindungan Situmeang; I Dewa Nyoman Sudita; Made Suarta; Ni Luh Putu Sulis Dewi Damayanti (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2023)
This study examines the impact of biochar and poschar fertilisers derived from livestock manure on red chilli yields and soil organic matter variations. The results demonstrated that the interaction between biochar and poschar substantially affected the fresh chilli pod weight per plant and organic matter content. Applying biochar and poschar organic fertilisers derived from animal manure substantially influenced plant height, fresh fruit weight per plant, and soil organic matter. The interaction between cow manure and poschar from poultry manure produced the highest yield of chilli fruit weight per plant, or an increase of 323.88% compared to the absence of biochar and poschar. The organic matter content of the soil underwent a significant change, with the highest organic matter content resulting from the interaction between chicken biochar and chicken poschar, which increased by 143,00% compared to the control group.